From Conflict to Inclusion in Housing The Interaction of Communities, Residents and Activists (University College London, 2017)
Socio-political views on housing have been brought to the fore in recent years by global economic crises, a notable rise of international migration and intensified trans-regional movement phenomena. Adopting this viewpoint, From Conflict to Inclusion in Housing maps the current terrain of political thinking, ethical conversations and community activism that complements the current discourse on new opportunities to access housing. Its carefully selected case studies cover many geographical contexts, including the UK, the US, Brazil, Australia, Asia and Europe. Importantly, the volume presents the views of stakeholders that are typically left unaccounted for in the process of housing development, and presents them with an interdisciplinary audience of sociologists, planners and architects in mind. Each chapter offers new interpretations of real-world problems, local community initiatives and successful housing projects, and together construct a critique on recent governmental and planning policies globally. Through these studies, the reader will encounter a narrative that encompasses issues of equality for housing, the biopolitics of dwelling and its associated activism, planning initiatives for social sustainability, and the cohabitation of the urban terrain.